2010
DOI: 10.21930/rcta.vol11_num1_art:190
|View full text |Cite
|
Sign up to set email alerts
|

Distribución espacial de Premnotrypes vorax (Hustache) (Coleoptera: Curculionidae) en cultivos de papa

Abstract: <p>La distribución espacial de los insectos plaga proporciona información importante para optimizar los programas de manejo y reducir la aplicación de insecticidas. En este trabajo se estudió la dinámica espacial de los adultos del gusano blanco Premnotrypes vorax en dos cultivos comerciales de papa durante 18 semanas. Durante este período se registró el número de adultos capturados semanalmente en 25 trampas de caída dispuestas en un diseño en cuadrícula. Además, se realizó la evaluación de los niveles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Comportamientos espaciales similares a los detectados para las poblaciones de Diatraea spp. han sido documentados para otras especies de insectos plaga, como es el caso de Jacobiasca lybica (Hemiptera: Cicadellidae) en viñedos (Ramírez et al 2002) y Premnotrypes vorax (Coleoptera: Curculionidae) en cultivos de papa (Pérez-Álvarez et al 2010).…”
Section: Parasitismo Por Enemigos Naturales En Larvas Y Huevos Deunclassified
“…Comportamientos espaciales similares a los detectados para las poblaciones de Diatraea spp. han sido documentados para otras especies de insectos plaga, como es el caso de Jacobiasca lybica (Hemiptera: Cicadellidae) en viñedos (Ramírez et al 2002) y Premnotrypes vorax (Coleoptera: Curculionidae) en cultivos de papa (Pérez-Álvarez et al 2010).…”
Section: Parasitismo Por Enemigos Naturales En Larvas Y Huevos Deunclassified
“…Adult insects of P. vorax feed on the plant leaves, but the most important damage with economic relevance is caused by the larvae, which feeds on the tubers, making galleries that affect the quality of the product showing external visible damage [6], resulting in up to 90% croploses due to the damaged tubers or to the complete crop destruction, especially when the larvae population is high [7]. It was reported that the life cycle of P. vorax can last up to nine months [8], indicating that it has only one or two generations per year.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the control of this insect by indigenous farmers involves extended crops rotation, special separation between fields, use of plant barriers, and chemical control with highly toxic chemical insecticides such as carbamates, pyrethroids, organophosphates and carbofuran that are applied at the time of potato planting. However, usually these insecticide treatments fail to penetrate deep in the soil, where the potato tuber grows [6,9]. In Colombia, more than US $22 million are spent each year for spraying insecticides against P. vorax [10].…”
Section: Introductionmentioning
confidence: 99%
“…P. vorax is distributed in South America, principally in Colombia, Ecuador, Venezuela and Peru with registries as one of the most important pests of potato (Solanum tuberosum) crops (Pérez et al, 2009). Adult insects feed on the plants and cause damage along the edges of the leaves, but the larvae also make tunnel-shaped lesions in the tubers causing externally visible damage (Pérez-Álvarez et al, 2010). This insect can cause commercial loses up to 80% of damaged tubers or the complete destruction of the potato crop, especially with high larvae populations (ICA, 2011).…”
Section: Introductionmentioning
confidence: 99%